Namizne družabne igre v šolski knjižnici - dodatna motivacija - Škrlj, Gregor (Šolska knjižnica, 2013)
The purpose of the paper is to encourage board-gaming in the school library. It describes the meaning of board-gaming which develops socialization and certain competences. Interest activity is described within which pupils learn to know different board games and to play them which teaches them to learn through play, adds more sense to certain contents and demonstrate that learning can be fun. The paper also presents board games which are based on literature which makes them good motivation for reading and exploring content, stories as well as authors of the literary works in question.
Keywords: igranje; motivacija; namizne družabne igre; osnovne šole; šolske knjižnice; učenje